Fostering Innovation in Community and Institutional Corrections Identifying High-Priority Technology and Other Needs for the U.S. Corrections Sector - Jackson, Brian A. (RAND Corporation, 2015)
Given the challenges posed to the U.S. corrections sector, such as tightened budgets and increasingly complex populations under its charge, it is valuable to identify opportunities where changes in tools, practices, or approaches could improve performance. In this report, RAND researchers, with the help of a practitioner Corrections Advisory Panel, seek to map out an innovation agenda for the sector.